The role of π-blocking hydride ligands in a pressure-induced insulator-to-metal phase transition in SrVO2H - Yamamoto, T; Zeng, D; Kawakami, T; Arcisauskaite, V; Yata, K; Patino, M; Izumo, N; McGrady, J; Kageyama, H; Hayward, M (Springer Nature, 2017)
Transition-metal oxyhydrides are of considerable current interest due to the unique features of the hydride anion, most notably the absence of valence p orbitals. This feature distinguishes hydrides from all other anions, and gives rise to unprecedented properties in this new class of materials. Here we show via a high-pressure study of anion-ordered strontium vanadium oxyhydride SrVO2H that H- is extraordinarily compressible, and that pressure drives a transition from a Mott insulator to a metal at ~ 50 GPa. Density functional theory suggests that the band gap in the insulating state is reduced by pressure as a result of increased dispersion in the ab-plane due to enhanced Vdπ-Opπ-Vdπ overlap. Remarkably, dispersion along c is limited by the orthogonal Vdπ-H1s-Vdπ arrangement despite the greater c-axis compressibility, suggesting that the hydride anions act as π-blockers. The wider family of oxyhydrides may therefore give access to dimensionally reduced structures with novel electronic properties.